Alternatives to Nuclear Overhauser Enhancement Spectroscopy Presat and Carr–Purcell–Meiboom–Gill Presat for NMR-Based Metabolomics - Le Guennec, Adrien (Anal Chem, 2017)
[Image: see text] NMR metabolomics are primarily conducted with 1D nuclear Overhauser enhancement spectroscopy (NOESY) presat for water suppression and Carr–Purcell–Meiboom–Gill (CPMG) presat as a T(2) filter to remove macromolecule signals. Others pulse sequences exist for these two objectives but are not often used in metabolomics studies, because they are less robust or unknown to the NMR metabolomics community. However, recent improvements on alternative pulse sequences provide attractive alternatives to 1D NOESY presat and CPMG presat. We focus this perspective on PURGE, a water suppression technique, and PROJECT presat, a T(2) filter. These two pulse sequences, when optimized, performed at least on par with 1D NOESY presat and CPMG presat, if not better. These pulse sequences were tested on common samples for metabolomics, human plasma, and urine.